STUDY OF CHAIRIL ANWAR "SUDAH GILA" DRAMA PERFORMANCE BASED ON DRAMA CHARACTERISTICS - Tohet, Moch; Hidayah, Nur; Mahbubi, M (Jurnal Buana Kata: Pendidikan, Bahasa, dan Ilmu Komunikasi, 2024)
This study aims to examine drama performances based on the characteristics of drama in one of Chairil Anwar's dramas entitled "Sudah Gila". The research method used is a qualitative approach through direct observation of the drama performances being analyzed. This drama was chosen as the object of research because it is a literary work that has high aesthetic and literary value and has been staged in the form of a drama. The research that will be discussed is regarding the study of drama performances which are analyzed based on the characteristics of drama. The results of this study are expected to provide a deeper understanding of the meaning and messages contained in Chairil Anwar's drama "Sudah Gila" through drama analysis.